COMPUTER MODELING OF AIR POLLUTION IN CASE OF DUST CLOUD MOVEMENT IN OPEN PIT MINE - Biliaieva, V. V.; Kirichenko, P. S.; Berlov, O. V.; Gabrinets, V. O.; Horiachkin, V. M. (Science and Transport Progress, 2019)
Purpose. Explosions in open pits lead to the formation of dust clouds. These clouds lead to intense air pollution. An important task is the development of methods for predicting the dynamics of atmospheric air pollution during explosions in open pits. The purpose of this work is development of a numerical model to predict atmosphere pollution after explosion in open mine pit. The task is to develop a numerical model that would allow for the calculation to take into account the geometrical shape of the open pit mine, the parameters of the meteorological situation (wind speed, atmosphere), the shape of the dust cloud that is formed in the open pit mine at the site of the explosion. Methodology. Mathematical modeling of dust cloud dispersion during an explosion in an open pit mine is based on the use of fundamental equations of aerodynamics and mass transfer. The airflow velocity field in the open pit mine is modeled using the Laplace equation for the velocity potential. The formation of the concentration field of dust is modeled on the basis of the equation of convective-diffusion dispersion of an impurity. For numerical integration of modeling equations, difference schemes are used. The Laplace equation for the velocity potential is numerically integrated using the Richardson method. For the numerical integration of the convective-diffusion dispersion equation for an impurity, an implicit difference splitting scheme is used. Findings. A CFD model has been developed that allows you to calculate the formation of pollution zones during the movement of a dust cloud in the open pit mine. A feature of the developed model is the speed of calculation. For practical use of the developed model, standard input information is required. Originality. In contrast to the existing models in Ukraine, the developed numerical model allows taking into account the geometrical shape of the open pit mine and the geometrical shape of the dust cloud when making predictive calculations to assess the level of air pollution caused by explosions in open pits. Practical value. The developed numerical model can be implemented on computers of low and medium power. For practical use of the numerical model, standard information on meteorological conditions in open pit mine is required. The numerical model can be used for environmental assessment of the effect of explosions in open pit mine on environmental pollution and work areas.